1990
DOI: 10.1093/nar/18.10.3035
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of RNA secondary structure, including pseudoknotting, by computer simulation

Abstract: A computer program is presented which determines the secondary structure of linear RNA molecules by simulating a hypothetical process of folding. This process implies the concept of 'nucleation centres', regions in RNA which locally trigger the folding. During the simulation, the RNA is allowed to fold into pseudoknotted structures, unlike all other programs predicting RNA secondary structure. The simulation uses published, experimentally determined free energy values for nearest neighbour base pair stackings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(119 citation statements)
references
References 40 publications
2
117
0
Order By: Relevance
“…The nearest-neighbor and hairpin loop values were taken from the updated set of parameters by D+ Turner and coworkers (http://www+ibc+wustl+edu/;zuker/rna/energy/index+shtml)+ When the stems contained bulges or internal loops, the loop and mismatch contributions were also taken into account+ For plant viral RNAs, we used the parameters for 25 8C, for animal RNAs, those for 37 8C+ For computer-assisted structure predictions, two algorithms, implemented in the package STAR, were used as described by Abrahams et al+ (1990) and Gultyaev et al+ (1995)+ …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nearest-neighbor and hairpin loop values were taken from the updated set of parameters by D+ Turner and coworkers (http://www+ibc+wustl+edu/;zuker/rna/energy/index+shtml)+ When the stems contained bulges or internal loops, the loop and mismatch contributions were also taken into account+ For plant viral RNAs, we used the parameters for 25 8C, for animal RNAs, those for 37 8C+ For computer-assisted structure predictions, two algorithms, implemented in the package STAR, were used as described by Abrahams et al+ (1990) and Gultyaev et al+ (1995)+ …”
Section: Methodsmentioning
confidence: 99%
“…Of course, the rough estimation presented does not take into account many additional effects that could be sequence-dependent+ NMR studies of a few pseudoknot structures provide evidence for loop interactions with helical grooves, which may diminish destabilizing energies (Kolk et al+, 1998)+ Possible positive enthalpic contributions in the loops were also suggested (Wyatt et al+, 1990)+ This means that a logarithmic approximation of the size dependence for loop entropies could be rather simplistic+ Also, the coefficient in the formula may slightly differ from 1+75, derived for loop closure by a base pair (Fisher, 1966), due to different excluded volume and end-to-end distance effects in pseudoknot loops+ Such effects are difficult to estimate because they should depend on a complex interplay between loop and stem dimensions, but they do not seem to lead to a considerable variation in the coefficient values+ As RNA pseudoknots are tertiary structure elements, Mg 2ϩ ion binding could be specific, with significant stabilizing effects (Puglisi et al+, 1991) and complex concentration dependence (Theimer et al+, 1998)+ Another important contribution to the stability is the stacking at the junctions between the coaxial stems, which could be influenced by some distortions+ On the other hand, even in bent pseudoknots an unpaired nucleotide at the junction is stacked with neighboring bases (Shen & Tinoco, 1995)+ Thus some deficiencies in our approximations could compensate for each other+ Without taking into account stabilizing or destabilizing sequence-specific energy contributions, we believe that the proposed parameters are valid with an accuracy of about 61 kcal/mol and could be used as rough approximations of pseudoknot stabilities and for computer predictions of structures+ Applying these parameters in the program STAR for RNA structure prediction (Abrahams et al+, 1990;Gultyaev et al+, 1995) did not result in an overrepresentation of pseudoknots in the predictions+ Although this is indirect evidence, it indicates that the proposed values do not overestimate pseudoknot stabilities significantly+ Compared to the previous estimate of the single value of 4+2 kcal/mol for all pseudoknot loops (Abrahams et al+, 1990), the current approximation suggests smaller or equal energies for short loops and greater values for large sizes, as expected+ Thus this approximation can improve the prediction programs, being able to predict proven pseudoknots without incorrectly predicted pseudoknotting due to possible un-derestimation of destabilizing effects in the loops by pseudoknot-including algorithms (Abrahams et al+, 1990;Gultyaev, 1991;Gultyaev et al+, 1995)+ Presumably, future experiments will improve these parameters and provide an opportunity to speculate about energies of more complicated pseudoknotted structures+…”
Section: Accuracy and Limitations Of The Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both impose restrictions on the kind of pseudoknots found in order to reduce the theoretical complexity of the problem, PKNOTS being more general (time complexity of O(n 6 ) and memory complexity of O(n 4 )) and pknotsRG more restrictive (O(n 4 ) for time and O(n 2 ) for memory). 1 …”
Section: Minimum Free Energymentioning
confidence: 99%
“…Abrahams et al [1] developed an algorithm that first finds all possible helices, then incrementally builds the final structure by selecting, at each step, the helix that minimizes the free energy of the current structure, allowing the introduction of pseudoknots. Schmitz and Steger developed a similar algorithm [129], but allowing the removal of current helices of the structure when the newly formed structure leads to pseudoknots or overlaps (bases participating in different helices).…”
Section: Kinetic Foldingmentioning
confidence: 99%